SPIRITUAL AND RELIGION CONCEPT IN NURSING FOR DIABETIC MELITUS PATIENTS - IWAN ARDIAN (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2016)
Diabetes is one of the chronic health problems and the psychological impact on the patient and is often associated with with several psychiatric disorders. Patients with diabetes were twice as likely to have status anxiety, depression and serious psychological problems. The psychological pressure of patients with diabetes mellitus often associated with the spiritual welfare and compliance religion. The limited information relating to the spirituality of the patient as well as their different views in interpreting spirituality and religion make less than optimal in increasing the spiritual wellbeing of patients that can ultimately help patients increase their quality of life. spirituality and religion how it can be distinguished patients with diabetes who have problems of spirituality and religion of patients who experienced an issue, because both have different concepts and dimensions.